Role of MyD88-adaptor-like gene polymorphism rs8177374 in modulation of malaria severity in the Pakistani population - Rani,Asima (2017)
Abstract Introduction: The present study was designed to investigate the association between rs8177374 polymorphism and malaria symptoms due to exposure of Plasmodium vivax and Plasmodium falciparum. Materials and methods: A total of 454 samples were included in the study (228 malaria patients and 226 healthy individuals). Malaria patients, divided into P. vivax and P. falciparum groups on the basis of the causative species of Plasmodium, were categorized into mild and severe on the basis of clinical outcomes according to WHO criteria. Healthy individuals were used as controls. Allele specific PCR based strategy was used for the identification of rs8177374 SNP. Results: MyD88-adaptor-like gene polymorphism was associated with susceptibility to malaria (p < 0.001). C allele frequency (0.74) was higher in the population compared to T allele frequency (0.26). CT genotype increased the susceptibility of malaria (OR: 2.661; 95% CI: 1.722-4.113) and was positively associated with mild malaria (OR: 5.609; 95% CI: 3.479-9.044, p = 0.00). On the other hand, CC genotype was associated with severe malaria (OR: 3.116; 95% CI: 1.560-6.224, p = 0.00). P. vivax infection rate was higher in CT genotype carriers compared to other genotypes (OR: 3.616; 95% CI: 2.219-5.894, p < 0.001). Conclusion: MyD88-adaptor-like/TIR domain containing adaptor protein polymorphism for single nucleotide polymorphism rs8177374 is related with the susceptibility of malaria.